Gait Analysis in Adults with Intellectual Disabilities Living in a Residential Facility. Issue 1 (22nd October 2015) - Salb, Johannes; Lindemann, Ulrich; Woodward, Carol; Almutaseb, Sanaa; Becker, Clemens; Sieber, Cornel; Freiberger, Ellen
Abstract : Background: Mobility limitations are of particular interest in people with intellectual disabilities. The aim of this study was to present feasibility and mean values of gait parameters in people with intellectual disability and it was hypothesized that several trials would be necessary to gain stable values for this cohort. Material and Methods: Thirty‐two adults with intellectual disability living in a residential facility were asked to do four walks in both normal and fast speed conditions over an instrumented walkway. Mean values of gait parameters were calculated over two different trial combinations, with TC1&2 representing the mean value of trials 1 and 2, and TC1‐4 representing the mean over all four trials. Results: All participants ( M age  = 59.6 years; SD = 16.71) successfully performed the protocol. Gait parameters remained constant over all trials. No significant differences were found between the trial combination TC1&2 and trial combination TC1–4. Conclusion: Gait analysis was found to be feasible in people with intellectual disability. Overall, the present authors recommend performing two trials and to calculate the means of gait parameters over these two trials to gain stable values.